August von Mackensen tábornagy 1935. évi magyarországi útja - Ligeti, Dávid (Közép-Európai Közlemények, 2019)
The German Field-Marshal August von Mackensen visited Hungary in May 1935. Despite the fact that the legendary WWI general had played an important role for the Kingdom of Hungary during the war, 1919 had been the year of his last visit. Mackensen was invited by Miklós Kozma, head of the Hungarian Press Agency (MTI), who had served as a hussar-officer in WWI. Moreover, Adolf Hitler sent a letter to Regent Miklós Horthy via Mackensen in order to strengthen German-Hungarian relations. Mackensen was received by the Hungarian people with great enthusiasm, for he had saved Hungary on three different occasions during the war: at the Gorlice breakthrough in May 1915, during the conquest of Serbia in autumn 1915 and with his counteroffensive against Romania in 1916, which had culminated with the occupation of Bucharest. On his visit, the German general visited war memorials and met with famous Hungarians, including Horthy, Prime Minister Gyula Gömbös and the former Austro-Hungarian Chief of Staff Artur Arz. Mackensen’s visit proved that German-Hungarian relations were not as robust and self-evident as portrayed later by Socialist-era historians. With the general’s visit, Hitler wanted to improve relations in order to ensure German dominance of Central Europe.